Q ‐switched and modelocked all‐fiber lasers based on advanced acousto‐optic devices - Cuadrado Laborde, Christian Ariel (2011)
The interest in all-fiber lasers is stimulated by the inherent advantages they have over bulk lasers in aspects such as heat dissipation and robustness. The performance of Q-switched and modelocked fiber lasers can benefit enormously from the development of all-fiber configurations. A fiber laser with strictly all-fiber components can fulfil the requirements of mechanical stability, low maintenance, enhanced power efficiency, simplified assembly process, and low cost. In this framework, recent developments infiber acousto-optic devices are reviewed that have demonstrated new possibilities for actively Q-switched distributed feedback fiber lasers, modelocking lasers and doubly active Q-switched modelocked lasers. The aim is to demonstrate the great potential of infiber devices for the active control of different types of fiber lasers.